2020
DOI: 10.1177/1049731520957415
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation Interventions in the United States: An Exploratory Investigation of Determinants and Impacts

Abstract: Purpose: To examine the determinants and impacts of implementing the mitigation interventions to combat the COVID-19 disease in the United States during the first 5 weeks of the pandemic. Method: A content analysis identified nine types of mitigation interventions and the timing at which states enacted these strategies. A proportional hazard model, a multiple-event survival model, and a random-effect spatial error panel model in conjunction with a robust method analyzing zero-inflated and skewed outcomes were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We report both of them and use the average in the precision-weighted average. ** The estimate from Guo et al (2021) is based on school closures in United States where all 50 states closed schools between March 13, 2020, andMarch 23, 2020, and44 states closed schools in just four school days (March 15, 2020 (Sunday) to March 19, 2020 (Friday)), see Table 1 in Auger et al (2020). Hence, the difference-in-difference effect is based on a maximum of seven school days.…”
Section: School Closuresmentioning
confidence: 99%
See 3 more Smart Citations
“…We report both of them and use the average in the precision-weighted average. ** The estimate from Guo et al (2021) is based on school closures in United States where all 50 states closed schools between March 13, 2020, andMarch 23, 2020, and44 states closed schools in just four school days (March 15, 2020 (Sunday) to March 19, 2020 (Friday)), see Table 1 in Auger et al (2020). Hence, the difference-in-difference effect is based on a maximum of seven school days.…”
Section: School Closuresmentioning
confidence: 99%
“…Hence, the difference-in-difference effect is based on a maximum of seven school days. As noted by Chernozhukov et al (2021), this lack of cross-sectional variation can lead to considerable uncertainty over the effects of school closures, and the results from Guo et al (2021) should be treated with this in mind.…”
Section: School Closuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Take social distancing as an example. A series of studies found that isolating infected people decreased and delayed transmission as well as reducing the epidemic’s peak [ 4 , 8 , 18 , 19 , 20 ]. Using counterfactual simulations, another study discovered that if the same restrictions on mobility had been implemented just one to two weeks earlier, a substantial number of cases and deaths would have been avoided.…”
Section: The Effect Of Government Response On the Infection Ratementioning
confidence: 99%